Geographies of Schooling - Jahnke, Holger; Kramer, Caroline; Meusburger, Peter (Knowledge and space, 2019)
Chapter 1. Territorial Governance of Schooling in Shrinking Regions -- Chapter 2. Local Educational Landscapes in Germany—Interfaces and Interlacings Between Education and Urban Development -- Chapter 3. School Autonomy Policies and the Changing Governance of Schooling -- Chapter 4. From Republican Spaces of Schooling to Educational Territories? The Problematic Emergence of Educational Territories in Post-Decentralized France -- Chapter 5. Ideology, Spatial Planning, and Rural Schools: From Interwar to Communist Hungary -- Chapter 6. Changing Structures and the Role of Education in the Development of the Educational System in Czechia -- Chapter 7. Securing Indigenous Dispossession Through Education: An Analysis of Canadian Curricula and Textbooks -- Chapter 8. Geopolitical Framings of Subalterity in Education: Compounding a Neoliberalized Welfare State -- Chapter 9. Bigger or Better? Research Based Reflections on the Cultural De-construction of Rural Schools in Norway—Meta Perspectives -- Chapter 10. A Multilevel View of Small Schools: Changing Systems in Baden-Württemberg and Vorarlberg -- Chapter 11. Small Rural Schools in Austria—Potentials and Challenges -- Chapter 12. Field and Terrain: The Micro-Politics of Community Leadership in Small, Rural Schools in England -- Chapter 13. Schools, Families and Social Reproduction -- Chapter 14. The Relationship Between School and Neighborhood—Child-Oriented Perspectives on Educational Locations -- Chapter 15. Redefining School: Educational Spaces for Adolescents’ Engagement in Learning -- Chapter 16. Feminization of Teaching: Female Teachers at Primary and Lower Secondary Schools in Baden-Wuerttemberg, Germany—From its Beginnings to the Present